GENERACIÓN DE VALOR AGREGADO EN LAS PYMES A TRAVÉS DE LA INNOVACIÓN EMPRESARIAL - Fairlie Frisancho, Ebor (2007)
The present study has evaluated small and micro-businesses of the districts of Village El Salvador, San Juan de Miraflores, San Martin of Porres, San Juan de Lurigancho and in La Victoria (Gamarra). The sample was of 20 in each district and 5 by each type of product. The sample it takes depending on the chosen products: crafts, carpentry/movable, making and leather/ footwear. The interview to the owners and/or responsible for the businesses was determined in base to questions designed and revised by experts, presenting validity and confiability. The comparisons in general showed that a 82% of PYMES that have applied some type of innovation in its business in the last 2 years they have seen increased its sales relating to its competitors, while those that it did not they do, alone an increment in the sales in a 27% of them has been reflected.